2008
DOI: 10.3758/pp.70.8.1471
|View full text |Cite
|
Sign up to set email alerts
|

Retention of high tactile acuity throughout the life span in blindness

Abstract: Previous studies of tactile acuity on the fingertip using passive touch have demonstrated an age-related decline in spatial resolution for both sighted and blind subjects. We have re-examined this age dependence with two newly designed tactile-acuity charts requiring active exploration of the test symbols. One chart used dot patterns similar to Braille and the other used embossed Landolt rings. Groups of blind Braille readers and sighted subjects, ranging in age from 12 to 85 years, were tested in two experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
117
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(137 citation statements)
references
References 51 publications
15
117
1
3
Order By: Relevance
“…2) are consistent with a number of previous studies (Brown & Stratton, 1925;Goldreich & Kanics, 2003;Legge et al, 2008;Stevens et al, 1996;Van Boven et al, 2000). Quantitatively, our results are quite similar to those of Goldreich and Kanics (2003;e.g., compare our results with their Fig.…”
Section: Discussionsupporting
confidence: 82%
“…2) are consistent with a number of previous studies (Brown & Stratton, 1925;Goldreich & Kanics, 2003;Legge et al, 2008;Stevens et al, 1996;Van Boven et al, 2000). Quantitatively, our results are quite similar to those of Goldreich and Kanics (2003;e.g., compare our results with their Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies report superior tactile spatial acuity in blind people (Stevens et al, 1996;Van Boven et al, 2000;Goldreich and Kanics, 2003;Legge et al, 2008), but what causes this enhancement? The extraordinary reliance of blind people in general, and Braille readers in particular, on the sense of touch might drive acuity enhancement (tactile experience hypothesis).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various perceptual properties that characterize object surfaces, roughness has undoubtedly received the most attention from haptics researchers. The roughness percept reflects the properties of the surface touched in interaction with the manner in which Studies have typically shown a decline in spatial acuity on the fingertip with increasing age for both sighted and blind individuals (e.g., Goldreich & Kanics, 2003;VegaBermudez & Johnson, 2004); for a more detailed summary, see Table 1 in Legge, Madison, Vaughn, Cheong, and Miller (2008). Studies that have used more recent psychophysical procedures further reveal that tactile spatial acuity in blind subjects is typically better than in sighted subjects who have been matched for age (but see Grant, Thiagarajah, & Sathian, 2000).…”
Section: Haptic Perception Of Object and Surface Propertiesmentioning
confidence: 99%
“…Most recently, however, Legge et al (2008) used two newly designed spatial-acuity charts that require active exploration of Braille-like dot patterns and raised Landolt rings ( Figure 3A). Their results confirmed earlier findings with sighted subjects-namely, a decline in tactile spatial acuity of almost 1% per year from 12 to 85 years (e.g., Stevens & Patterson, 1995); in contrast, the blind showed high tactile spatial acuity that did not decline with age and that was not limited to the finger used for reading Braille ( Figure 3B).…”
Section: Haptic Perception Of Object and Surface Propertiesmentioning
confidence: 99%